Analysis of blood lactate and heart rate of indoor sports athletes as a response to various loads - Arslan Kalkavan; Aydın Senturk; Halit Harmancı; Ismail Kaya; M Karavelıoglu; Meryem Savaslı; Oguzhan Yuksel (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to analyse the changes in blood lactate and heart rate levels of indoor sports athletes as a response to various loads in cycle ergometer.  The participants of the study are 28 male volunteer athletes of indoor sports active in basketball, volleyball, handball league. Age: 21.00 ±1.56 years, height: 181.54 ± 7.67 cm, weight: 83.04 ± 10.69 kg. Heart rate and lactate measurements of the subjects were taken from their fingertips at rest and following every load increase. With the initial load of 1 kg, the subjects were exposed to 0.5 kg load increase every three minutes. Since only 3 subjects completed with the final load of 4.5 kg, the values of this load was excluded. Pearson multiplications Moment Correlation was used to determine the relation between the load increase of the groups and their heart rate and between the load increase of the groups and their blood lactate values. The test results revealed a significant relation between the load means applied on the subjects and their heart rate at the rate of -0.99; between the applied load means and blood lactate at the rate of 0.97.